(untitled) (Research, Society and Development, 2022)
Non-steroidal anti-inflammatory drugs (NSAIDs) are used in third molar extraction due to their anti-inflammatory, analgesic and antipyretic effects in the control of postoperative pain, swelling and trismus. Therefore, this study aimed to describe the effectiveness of NSAIDs as drug therapy, combined or isolated with opioids in the preoperative period in oral surgery of third molars. This is an integrative review study. For this, descriptors registered in DeCS/MeSH were applied in the indexed databases of PubMed, LILACS, IBECS and BBO and later interconnected through the Boolean operator “and”. A total of 109 studies over a 5-year period (2018 to 2022) were retrieved. After analysis, 13 clinical trials with or without randomization were included. The literature shows promising effects on the therapeutic action of NSAIDs when administered preemptively for tooth extraction of third molars, showing a reduction in anti-inflammatory responses, contributing to a faster recovery of patients. Sodium diclofenac, meloxicam, nimesulide, ibrupofen, trometamol and flurbiprofen were efficient in controlling inflammatory events, contributing to the reduction of redness, edema, trismus and pain in the observed studies. The combination or not of NSAIDs with opioids significantly reduces pain, swelling and trismus in third molar extraction. However, new clinical trials with prolonged periods and significant samples should be designed in order to conceptualize which combinations and their respective pharmacological dosages may present better analgesic efficacy.